2015
DOI: 10.1080/03630242.2015.1101741
|View full text |Cite
|
Sign up to set email alerts
|

Association of intimate partner violence and health-care provider-identified obesity

Abstract: We examined the association of physical and non-physical IPV (intimate partner violence) with obesity. Women (n=1,179) were surveyed regarding demographics, obesity, and IPV exposure using HARK (humiliate-afraid-rape-kick), an IPV screening tool. A three-level lifetime IPV exposure variable measured physical, non-physical or no IPV. Healthcare provider-identified obesity was defined if participants were told by a medical provider within the past 5 years that they were obese. Bivariate analyses examined obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
3
13
0
5
Order By: Relevance
“…Surprisingly, we did not nd any signi cant association between IPV and underweight, relative to normal weight. While this nding is consistent with some studies [74,85], others suggest that exposure to IPV increases the odds of being underweight [85,86]. These inconsistent ndings may be attributed to study population, demographic and socioeconomic contexts [18,26,85].…”
Section: Dicussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Surprisingly, we did not nd any signi cant association between IPV and underweight, relative to normal weight. While this nding is consistent with some studies [74,85], others suggest that exposure to IPV increases the odds of being underweight [85,86]. These inconsistent ndings may be attributed to study population, demographic and socioeconomic contexts [18,26,85].…”
Section: Dicussionsupporting
confidence: 87%
“…The ndings further revealed that women of reproductive age are at high risk of excess weight [31,73,74], as more than one-fth reported being overweight and about 12% obese. Several studies have reported overweight and obesity to be on the rise in developing countries [29,31,33], and risk factors such as high economic status, urban residence [75,76], and, indeed, intimate partner violence [77,78] have been implicated.…”
Section: Dicussionmentioning
confidence: 89%
“…If a woman is screened for anxiety or depression during pregnancy, further screening undertaken in the postpartum period should also be considered 124 . Intimate partner violence has also been associated with obesity 125,126 . Experiencing intimate partner violence is associated with weight gain over time and depressed mood further augments weight gained 127 .…”
Section: Figo Guidance For Pregnancy Obesitymentioning
confidence: 99%
“…It is a persistent stressor in women's lives (Anderson & Saunders, ; Goodman, Smyth, Borges, & Singer, ) leading to a significant proportion of mental and physical health issues (Devries et al., ; García‐Moreno et al., ). Two studies have found a correlation between IPV and obesity (Sato‐DiLorenzo & Sharps, ; Silva, Irabor, Olowookere, Owoaje, & Adebusoye, ) and seven studies found that IPV was a predictor of obesity (Bosch, Weaver, Arnold, & Clark, ; Breiding, Black, & Ryan, ; Clark et al., ; Davies, Lehman, Perry, & McCall‐Hosenfeld, ; Mason, Ayour, Canney, Eisenberg, & Neumark‐Sztainer, ; Scott‐storey, Wuest, & Ford‐gilboe, ; Yount & Li, ). While the studies that used correlational and regression analyses provide valuable insight, they were limited in showing the pathway through which IPV leads to obesity.…”
Section: Introductionmentioning
confidence: 99%